PARTISIPASI PETANI DALAM PEMBANGUNAN IRIGASI ANAI DUA DI NAGARI SINTUK KECAMATAN SINTUK TOBOH GADANG KABUPATEN PADANG PARIAMAN - Asmi, Novri Yani; Dasrizal, Dasrizal; Prarikeslan, Widya (STKIP PGRI Sumbar, 2013)
This study aims to determine the participation of farmers in irrigation development Anai Dua in NagariÂ Sintuk Toboh Gadang District Padang Pariaman. This research is descriptive. The population in this study were all farmers living in Sintuk Toboh Gadang, amounting to 1.536 people. Sample were taken in 2 ways, the sample area is Jorong Balai Usang, Tanjung Pisang dan Batang Tapakis located near irrigation development, while the sample were taken with a proportional random sampling technique with a proportion of 10% so that the total sample of 66 people. The research found that: 1) Participation from the attention of farmers on irrigation Anai Dua average score was 3.39 with 67.68% respondents level of achievement on the criteria that are good, 2) participation of responsibility farmer seen its average score is 3.86 with 77.27% of respondents level of achievement that is in pretty good criteria and 3) Participation views of farmers on irrigation development action Anai Dua average score was 2.85 with 57.05% of respondents achievement levels that are at criteria are less well